The role of technology: Community based service-learning projects on ethical development - Ruso, Nazenin (My University, 2012)
This study explores the utility of CBSL (community based service-learning) projects as a teaching method of ethics which this process supported by online communication tools in order to enhance progress of service learning and ethical development of undergraduate students and gather data during the research process. This study consists of an action research project and it employs case study method as it attempts to explore a unique phenomenon (CBSL projects) in Eastern Mediterranean University. Triangulation, which involves different methods to gather information, were preferred and the desired data were collected through pre-test, post-test, reflective papers and semi-structured interviews. This research identifies the critical question in the affective domain of learning such as the possibility of affecting students' ethical values in undergraduate years. The results of this study are noteworthy and clearly reflect that CBSL projects lead empowering and worthwhile experiences. Major findings are suggestive of a positive change basically in students' moral development, future awareness and empathy due to CBSL exposure. © The Turkish Online Journal of Educational Technology.
Keywords: Empathy; Future awareness; Moral development; Technology